Analytical solutions for fully developed laminar flow of some viscoelastic liquids with a newtonian solvent contribution - Cruz, D. O. A. (2010)
Made available in DSpace on 2010-04-28T10:07:13Z (GMT). No. of bitstreams: 1 ri47.pdf: 219735 bytes, checksum: 27f70de6e668fd509162b82130f7dd29 (MD5)